Performance of the inFLUenza Patient-Reported Outcome Plus (FLU-PRO Plus) Instrument in Patients With Coronavirus Disease 2019. (8th October 2021) - Richard, Stephanie A; Epsi, Nusrat J; Pollett, Simon; Lindholm, David A; Malloy, Allison M W; Maves, Ryan; Utz, Gregory C; Lalani, Tahaniyat; Smith, Alfred G; Mody, Rupal M; Ganesan, Anuradha; Colombo, Rhonda E; et al.
Abstract: Background: The inFLUenza Patient-Reported Outcome Plus (FLU-PRO Plus) is a patient-reported outcome data collection instrument assessing symptoms of viral respiratory tract infections across 8 body systems. This study evaluated the measurement properties of FLU-PRO Plus in a study enrolling individuals with coronavirus disease 2019 (COVID-19). Methods: Data from a prospective cohort study (EPICC) in US Military Health System beneficiaries evaluated for COVID-19 was utilized. Adults with symptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with FLU-PRO Plus survey information within 1 week of symptom onset were included. Reliability of FLU-PRO Plus was estimated using intraclass correlation coefficient (ICC; 2 days' reproducibility). Known-groups validity was assessed using patient global assessment (PGA) of disease severity. Patient report of return to usual health was used to assess responsiveness (day 1–6/7). Results: Two hundred twenty-six SARS-CoV-2–positive participants were included in the analysis. Reliability among those who reported no change in their symptoms from one day to the next was high for most domains (ICC range, 0.68–0.94 for day 1 to day 2). Construct validity was demonstrated by moderate to high correlation between the PGA rating of disease severity and domain and total scores (eg, total scores correlation: 0.69 [influenza-like illness severity], 0.69 [interference in daily activities], and –0.58 [physical health]). In addition, FLU-PRO Plus demonstrated good known-groups validity, with increasing domain and total scores observed with increasing severity ratings. Conclusions: FLU-PRO Plus performs well in measuring signs and symptoms in SARS-CoV-2 infection with excellent construct validity, known-groups validity, and responsiveness to change. Standardized data collection instruments facilitate meta-analyses, vaccine effectiveness studies, and other COVID-19 research activities.